Student Motivation in Learning Football Games at SMAN 3 Purwakarta (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to determine the level of student motivation in learning soccer games for class X at SMAN 3 Purwakarta. This type of research is descriptive quantitative with the use of a questionnaire via Google Forms as a research instrument using a 5-point Likert scale. The population in this study were all class X students at SMAN 3 Purwakarta, namely 427 students. The sample in this study was 206 students, the result of calculations using the Slovin formula. The use of descriptive statistics in data analysis with percentages as an explanation of the results of the study. The results of this study show that student motivation in soccer games at SMAN 3 Purwakarta, in detail, has less criteria with a percentage of 63.4%, and has several factors, namely internal factors have 64.8%, while external factors have a percentage of 58%. So this study can conclude that student motivation in learning soccer games at SMAN 3 Purwakarta is in the lower category.